Are hypertrophic astrocytes a sufficient criterion of perinatal telencephalic leucoencephalopathy? - Leviton, Alan (1973)
To determine if the presence of amphophilic globules (GL) in infant cerebral white matter was a necessary criterion of perinatal telencephalic leucoencephalopathy (PTL), the epidemiological features of infants who had PTL—that is, hypertrophic astrocytes and amphophilic globules (HA·GL)—in their cerebral white matter were compared with those of infants who had hypertrophic astrocytes, but who did not have amphophilic globules (HA·[unk]). Postmortem bacteraemia was seen much more frequently in infants with HA·GL than in infants with HA·[unk] (P<0·05). In addition, infants with HA·GL tended to die at older postnatal ages than infants with HA·[unk]. These observations are in keeping with the view that HA·GL and HA·[unk] are not epidemiologically identical. The operational definition of PTL therefore remains the occurrence of both HA and GL in infant cerebral white matter.